NATURALISM IN THE SHORT STORY OF WILLIAM FAULKNER’S “A ROSE FOR EMILY’ - Rita Napitupulu (Jurnal Bahasa Indonesia Prima (JBIP), 2021)
Abstract A Rose For Emily is a short story by Mississippi born William Faulkner, first published in 1930. This story does not tell only about a lonely woman but also tells about a person who is forced to lead an isolated life; it is about her mental state due to her abused childhood that made her isolate herself. She lived in isolated. The vicitudes of Miss Emily’s life remain a mystery until the very end of the story. Although the actions are not visible to the reader, but the narrator evidently describes herphysical appearance and the environtment she lives in. The detailed characterization resembles Naturalist literary characterization – an accurate description of the protagonist’s deplorable physical condition and a pessimist and negative vision of the character.Furthermore the realistic description of Miss Emily’s house highlights the decaying image of the setting, that reflects the protagonist’s own state of mind. The surprising end of the story is also a common characteristic in Naturalist narration. There is a considerable amount of social impact and paternal influence reflected in Emily’s isolated and neurotic state of mind and this similarity proves the Naturalist point view of life- human s are conditioned by gebelogical, family and social condition. Naturalism in the Short Story of William Faulkner ‘s A Rose for Emily, is as the title of her research and the objective of this research is to find out the elements of Naturalism in the short story of William Faulkner’s A Rose for Emily and why those elements are found in the short story. The methodology used in this research is the descriptive qualitative method. The findings of the research are 2 (two) elements of Naturalism, they are Determinism and Setting. Those elements are found in the short story are William Faulkner wants to tell that Emily’s father is as the cause that makes her not married until die. Her father is the one man who keeps her single by chasing away all her suitors as it can be seen through the analysis in part 4.1.1 and part 4.1.2. Besides that, the present generations that cannot accept her, coz of the past law that concerns with the tax pay which makes her free from the payment in past law. The status of the persons that come from the different locations, such as Emily from the South and Homer from the North. Between the aristocratic person and the laborer that become an obstacle in their relationship. Key words : Naturalism, Elements of Naturalism, Environtment, Sociology of Literature, Short Story